Pastoral Care and the Caring Teacher : Value Adding to Enabling Education. - Seary, Karen; Willans, Julie (Student Success v.11 n.1 p.12-21 https://doi.org/10.5204/ssj.v11i1.1456, 2020)
The concept of pastoral care to effectively meet the personal, social and academic needs of students is a complex yet under-researched matter in higher education. Similarly, under-researched and institutionally undervalued is the pivotal role that the caring teacher fulfils in imbuing pastoral care in enabling courses. Using an enabling course in a regional Australian university as the context, this article outlines the concept of pastoral care and then discusses the characteristics of the caring teacher, so fundamental to enabling education. The article draws on Motta and Bennett's (2018) pedagogies of care, namely care as recognition, care as dialogic relationality, and care as affective and embodied praxis to analyse how the students perceived and valued care in the enabling course in which they participated. Findings indicate that supportive learning environments in which caring teachers nurture their students can promote very positive interactions, and ultimately, high student satisfaction and retention. [Author abstract]